Effect factors on thermal and mechanical properties of SiO2 and TiB2 modified SiBCN-based adhesives. Issue 11 (1st August 2020) - Luan, Xin'gang; Li, Min; Chang, Sen; Li, Yongguo; Wang, Kunjun; Song, Xuemei; Riedel, Ralf; Cheng, Laifei
Abstract: To further investigate the reinforcing factors on the adhesion strength of SiO2 and TiB2 modified SiBCN-based adhesives, the thermal stability analysis, microstructure observations and phase composition analysis were performed on four kinds of modified PSNB (Polyborosilazane) adhesives. With the different Si/B ratio and SiO2 content, the room temperature adhesion strength reach up to 18.95, 12.04, 32.44 and 13.69 MPa for PPT-1, PPT-2, PPTS and PST respectively, after synthesized at 1000 °C in air. And then, the high temperature adhesion strength reach up to 12.3 and 16.4 MPa for PPT-1 and PPTS at 1000 °C in vacuum, respectively. Interestingly, it has been found that temperature, PSO, solid content and SiO2 content all have a great influence on the adhesion performance of SiO2 and TiB2 modified SiBCN-based adhesives.